Penerapan Corporate Social Responsibility dengan Konsep Community Based Tourism - Linda Suriany (FISIP Universitas Atma Jaya Yogyakarta, 2008)
Abstract: Business is not only economic institution, but social institution too. As social institution, business has responsibility to help society in solving social problem. This responsibility called Corporate Social Responsibility (CSR). CSR pays attention about social problem and environment, so CSR support continuous development to help government role. Nowadays, our government has national development’s agenda. One of them is tourism sector (Visit Indonesia Year 2008 programmed). But tourism sector has challenge in human resources. In this case, business role in practice CSR is needed to help tourism sector. With CSR activities, the quality of local community will increase to participate in tourism activities. CSR activities include training that based on research. When the quality of local community increase, local community can practice the concept of community based tourism (CBT). In the future, Indonesia has a power to compete with other countries.